Rome foundation Asian working team report: Real world treatment experience of Asian patients with functional bowel disorders. Issue 8 (August 2017) - Xiong, Lishou; Gong, Xiaorong; Siah, Kewin Tien‐Ho; Pratap, Nitesh; Ghoshal, Uday Chand; Abdullah, Murdani; Syam, Ari Fahrial; Bak, Young‐Tae; Choi, Myung‐gyu; Lu, Ching‐Liang; Gonlachanvit, Sutep; Chua, Andrew Seng Boon; et al.
Abstract: Background and Aim: Information on real world treatment experiences of patients with functional bowel disorders is lacking from Asia. This study aimed to describe the medication exposure and treatment satisfaction of patients presenting to gastroenterology clinics across a sampling of Asian cities. Methods: From March 2011 to October 2013, adult patients presenting to hospital‐based gastroenterology outpatient clinics in 11 cities across Asia, who fulfilled screening criteria for any functional gastrointestinal disorder, were asked to complete a validated culturally adapted translation of the Rome III diagnostic questionnaire, a checklist of medications received in the preceding 3 months and questions on treatment satisfaction. Results: A total of 1376 patients (female 755, male 621, 41.36 ± 13.25 years) comprising irritable bowel (621, 45.1%), unspecified functional bowel disorder (372, 27.8%), functional constipation (202, 14.7%), functional bloating (144, 10.5%), and functional diarrhea (56, 4.1%) completed the study. Of 1105 patients with a previous consultation, 509 (46.1%) were dissatisfied with their treatment, with ineffective treatment being the commonest reason. Satisfaction with previous consultation was lowest by diagnosis for functional constipation (29.2%), and the most bothersome symptom was straining (37.5%). Of 1046 patients who had taken medications for their gastrointestinal symptoms in the last 3 months, 793 (75.8%) had received two or more drugs. For irritable bowel syndrome patients, treatment with proton pump inhibitors and antispasmodics was recorded in 57% and 31%, with overlapping epigastric pain and heartburn predicting proton pump inhibitors use. Conclusions: More attention should be given to treatment gaps with regards to possible under‐treatment with antispasmodics in irritable bowel syndrome and to critically evaluating the efficacy of constipation management.